2012
DOI: 10.1080/0092623x.2011.606883
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Treatment of Antipsychotic-Induced Sexual Dysfunction and/or Hyperprolactinemia Among Patients of the Schizophrenia Spectrum: A Review

Abstract: There is limited evidence for the management of sexual dysfunction and/or hyperprolactinemia resulting from use of antipsychotics in patients with schizophrenia and spectrum. The aim of this study was to review and describe the strategies for the treatment of antipsychotic-induced sexual dysfunctions and/or hyperprolactinemia. The research was carried out through Medline/PubMed, Cochrane, Lilacs, Embase, and PsycINFO, and it included open labels or randomized clinical trials. The authors found 31 studies: 25 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 56 publications
0
23
0
1
Order By: Relevance
“…In most studies on switching strategies of antipsychotics or adding a dopamine agonist, an increase in psychotic symptoms is not frequently reported. 97,98 In our clinical experience, switching medication in collaboration with the patient, with the explicit aim of finding the best tolerated antipsychotic that is still effective, nearly always leads to a better outcome, although sometimes a return to the original antipsychotic may be necessary.…”
Section: Pharmacological Treatment Strategies For Antipsychotic-inducmentioning
confidence: 99%
See 3 more Smart Citations
“…In most studies on switching strategies of antipsychotics or adding a dopamine agonist, an increase in psychotic symptoms is not frequently reported. 97,98 In our clinical experience, switching medication in collaboration with the patient, with the explicit aim of finding the best tolerated antipsychotic that is still effective, nearly always leads to a better outcome, although sometimes a return to the original antipsychotic may be necessary.…”
Section: Pharmacological Treatment Strategies For Antipsychotic-inducmentioning
confidence: 99%
“…The switch from risperidone to quetiapine was demonstrated in 2 randomized controlled studies, with one showing improvement in sexual functioning and lowering of prolactin levels. 72,104 Open label studies 98 reported improved sexual functioning for adjunctive therapy with aripiprazole, [104][105][106] vardenafil, 108 peony-glycyrrhiza-decoction, 109 carbegoline, 110 amantadine, 111,112 shakuyaku-kanzo-to 113 , and imipramine. 114 Open label studies described improvement in sexual performance when switching from antipsychotics that are strong dopamine antagonists (which often lead to elevated prolactin levels) to aripiprazole, 105,[115][116][117] ziprasidone, 118,119 olanzapine [120][121][122][123] , and quetiapine 124,125 (prolactin sparing antipsychotics); the switch to aripiprazole was the most studied strategy.…”
Section: Pharmacological Treatment Strategies For Antipsychotic-inducmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it is important to try to understand the influence of sexuality on the individual's overall quality of life, in order to assess the need for adjusting treatment. Proper knowledge about the different pharmacological properties of antipsychotics which have effect on sexual performance may be helpful in choosing antipsychotic with a low risk of inducing sexual side effects [13]. Proper follow up is required as there is a chance of reduction in patient compliance to prescribed antipsychotics, when they identify the sexual dysfunction.…”
Section: Methods To Manage Sexual Dysfunction In Patients Taking Antimentioning
confidence: 99%